Music teacher perceptions of modern band and Little Kids Rock: a qualitative study of programme outcomes. (15th March 2023) - Knapp, David H.; Powell, Bryan; Smith, Gareth Dylan
ABSTRACT: Music education in the United States is typified by students in large ensembles, like band and orchestra, learning to perform pieces of Western art music. One organisation working to expand curricular offerings within the field is Little Kids Rock (LKR), which has invested millions of dollars training music teachers and providing instrument resources for popular music pedagogy. Though this organisation has demonstrated success in its ability to propagate 'modern band' programmes, the effects of its investment are not known. LKR administers an end-of-year survey to its participating teachers to assess teachers' perceptions of their music programmes. However, LKR do not publish meaningful information regarding the outcomes and impact of its activities. The present study examined free-response data from the 2018 end-of-year survey. Using the passive and active identity and learning realisation (PAILR) model as our analytical framework (Froehlich, Hildegard C., and Gareth Dylan Smith. 2017. Sociology for Music Teachers: Practical Applications. 2nd ed. New York: Routledge. doi:10.4324/9781315402345), the authors analysed themes using grounded theory to produce a logic model to describe the effects of LKR's investment. Results indicate participating teachers perceive a positive impact on students, including being more engaged in their learning, and more musically independent. Additionally, teachers believed they were more engaged and committed to their profession, and more able to teach previously disengaged students.